Gitti's Story Earth - Anushka Kalro (Tulika Publisher India, 2012)
"Gitti, the rock, is very old. After a long, long journey that started from the boiling hot centre of the earth, he now sits quietly on a mountain, watching the sun rise and set. What is his story?"--Cover page 4.
Keywords: Read Aloud -- Read Aloud; PY - UOI / How The World Works / Earth -- PY - UOI / How The World Works / Earth